2007
DOI: 10.2337/db05-1334
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose, High Insulin, and Their Combination Rapidly Induce Laminin-β1 Synthesis by Regulation of mRNA Translation in Renal Epithelial Cells

Abstract: Laminin is a glycoprotein that contributes to renal extracellular matrix expansion in diabetes. We investigated regulation of laminin-␤1 synthesis in murine renal proximal tubular epithelial cells by 30 mmol/l glucose (high glucose), 1 nmol/l insulin (high insulin), and their combination (high glucose؉high insulin), simulating conditions observed during progression of type 2 diabetes. Compared with 5 mmol/l glucose and no insulin (control), high glucose alone, high insulin alone, or high glucose؉high insulin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
88
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 52 publications
11
88
1
Order By: Relevance
“…48,49 Several studies have also suggested that mTOR activation has a crucial role in the pathogenesis of kidney hypertrophy and increase of matrix proteins in the GBM in diabetic nephropathy. 50,51 However, to our knowledge, there has been only one report on the role of mTOR activation in anti-GBM nephritis showing that pretreatment of rapamycin protected glomerular injury through affecting T-and B-cell activation. 52 However, the typical glomerular change in their animal model was severe mesangial expansion and not CGN.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Several studies have also suggested that mTOR activation has a crucial role in the pathogenesis of kidney hypertrophy and increase of matrix proteins in the GBM in diabetic nephropathy. 50,51 However, to our knowledge, there has been only one report on the role of mTOR activation in anti-GBM nephritis showing that pretreatment of rapamycin protected glomerular injury through affecting T-and B-cell activation. 52 However, the typical glomerular change in their animal model was severe mesangial expansion and not CGN.…”
Section: Discussionmentioning
confidence: 99%
“…Acute Effects of Ang II on Fibronectin Synthesis and Deposition-It has been proposed that recurrent acute stimulation of extracellular matrix protein synthesis by renal cells participates in the significant expansion of matrix leading to fibrosis in kidney disease (52). This observation prompted us to investigate the effect of short term exposure of MCs to Ang II on the fibronectin synthesis and deposition.…”
Section: Involvement Of Src In Ang Ii-induced Pdk-1 Tyrosinementioning
confidence: 99%
“…To further substantiate our results, we employed a loss-of-function strategy. We used an adenovirus vector expressing a dominant negative FoxO1 that inhibits FoxO1-dependent transcription ( FoxO1 Regulates High Glucose-induced mTORC1 ActivationWe have shown recently that high glucose activates mTORC1 in an Akt kinase-dependent manner (5,8,11,27). This activation of mTORC1 occurs via Akt-dependent phosphorylation of PRAS40, which is a component and negative regulator of mTORC1.…”
Section: High Glucose-induced Foxo1 Phosphorylation Regulates Aktmentioning
confidence: 99%
“…We and others have shown a significant role of this kinase cascade in inducing renal hypertrophy and matrix expansion in diabetic animals and in cultured mesangial and proximal tubular epithelial cells (5)(6)(7)(8)(9)(10). Our recent observation that hyperglycemia reduces the tumor suppressor protein PTEN (phosphatase and tensin homolog deleted on chromosome 10), which acts as a lipid phosphatase to dephosphorylate the PI 3,4,5-trisphosphate, also contributes to the hyperactivation of Akt in diabetic renal glomeruli and in mesangial cells, therefore providing an additional mechanism of Akt activation in diabetic kidney disease (7,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation